Fostering Students' Arabic Learning Motivation: The Synergy of Quantum Teaching and Monopoly-Based Media - Dedih Wahyudin; Odang Odang; Saskia Siti Silvia (UIN Sunan Gunung Djati Bandung, 2026)
Student motivation remains a major challenge in Arabic language learning, particularly in classrooms where conventional instructional approaches provide limited opportunities for active engagement. Although Quantum Teaching and game-based learning have independently demonstrated positive effects on student learning, empirical studies examining their integration in Arabic language education remain limited. This study aims to investigate the effectiveness of integrating the Quantum Teaching model with Monopoly Game Smart, an educational game designed to promote interactive and meaningful learning experiences, in enhancing students' motivation to learn Arabic. A quantitative quasi-experimental design employing a pre-test–post-test control group was used. The participants were eighth-grade students at MTs Darul Hikam Banjaran assigned to experimental and control groups. Data were collected through a learning motivation questionnaire and supported by classroom observations and interviews. Quantitative data were analyzed using N-Gain and an independent-samples t-test. The findings revealed that the experimental group achieved significantly greater improvement in learning motivation than the control group (p < 0.05), with a moderate gain, compared to the low gain observed in the control group. Classroom observations also indicated higher levels of participation and engagement among students receiving the intervention. These findings suggest that integrating Quantum Teaching with Monopoly Game Smart provides an effective instructional strategy for fostering motivation and active participation in Arabic language learning. The study contributes empirical evidence supporting the use of game-based innovations within the Quantum Teaching framework to enhance student engagement in Arabic language education.